A Novel Variant in Non-coding Region of GJB1 Is Associated With X-Linked Charcot-Marie-Tooth Disease Type 1 and Transient CNS Symptoms - Luo, Si; Jin, Hui; Chen, Jiajun; Zhang, Lei (Frontiers in Neurology, 2019)
X-linked Charcot-Marie-Tooth disease type 1 (CMTX1) is a dominantly inherited peripheral neuropathy and is caused by mutations in gap junction beta 1 gene (GJB1). Here, a novel variant of c.-170T>G in GJB1 was identified in a large Chinese CMTX1 pedigree. The proband presented transient “stroke-like” episodes in addition to the peripheral neuropathy. At the time of episode, he had transient hyperthyroidism. To our knowledge, this is the first variant found in noncoding region associated with transient central nervous system (CNS) symptoms and in this case, thyroid dysfunction might contribute to the episode. The mechanism of CMTX1 as well as the transient CNS symptoms waits to be elucidated.